Experimental investigation of solar parabolic trough collector with a helical coil receiver under Jordan climate conditions - Okour, Mohammed; Q. Al-Odat, Mohammad (International Journal of Engineering and Technology, 2019)
This paper presents an experimental study of parabolic trough solar collector (PTC) with a helical recovers performance under Irbid-Jordan (32.50 N, 35.90 E) climate conditions. The collector was tested during selected days of December, 2014. The various parameters affecting the problem under investigation are including solar radiation intensity, the inclination and tilt angles, and the heat transfer from the beam radiation reflecting to the reserve was investigated. The performance of PTC was evaluated by using outdoor experimental measurements including the outlet temperature of water and the thermal instantaneous efficiency. The experimental measurements for average thermal efficiency and outlet temperature for the water is approximately 64.7% and 55 ËšC respectively, while the theoretical calculation is 69.4% and 57.5ËšC respectively.Â Â Â